The bispecific antibody targeting VISTA and PD-L1 shows enhanced tumor inhibitory activity in pancreatic, endometrial and breast cancers compared to mono- and combination immune checkpoint blockade - Bielski, Przemysław; Barczyński, Jan; Mikitiuk, Michał; Myrcha, Maja; Rykała, Kamil; Boon, Louis; Gąsior, Wiktoria; Hec-Gałązka, Aleksandra; Holak, Tad A.; Sitar, Tomasz (Frontiers in Immunology, 2025)
BackgroundThe introduction of checkpoint immunotherapeutic agents in the last decade has revolutionized cancer treatment. Although anti-PD-1, anti-PD-L1 and anti-CTLA4 are promising therapies, many patients fail to respond or relapse due to drug resistance potentially due to redundancy of immune checkpoints. One of the ways to improve the efficacy of this cancer treatment is to target two or even three immune checkpoints. To date, the benefit of combined anti-VISTA/anti-PD-L1 therapy has been confirmed, but no one has investigated the efficacy of blocking these negative immune checkpoints with a bispecific anti-VISTA/anti-PD-L1 antibody.MethodsIn this study, the bispecific antibodies (bsAbs) were produced in three formats: symmetric (IgG-HC-scFv), asymmetric (Fab-scFv-Fc(KIH)) and 2 x scFv. The binding and blocking properties of these bispecific antibodies (bsAbs) and their efficacy compared to monotherapy and combination therapy were then determined using endometrial (RL95-2), pancreatic (PANC-1) and breast (BT-20) cancer cell lines.ResultsThe bsAbs generated in this study showed weaker binding properties to PD-1 and VISTA in ELISA (EC50) than the parent antibodies (atezolizumab and onvatilimab). Blockade of VISTA/VSIG-3 binding was also weaker with bsAbs compared to onvatilimab, but the ability to block the PD-1/PD-L1 pathway was slightly better than with atezolizumab. The Fc-based bsAbs showed statistically significant higher levels of lysis of endometrial, breast and pancreatic cancer cells. The symmetric bsAbs (IgG-HC-scFv) showed the most promising therapeutic potential. Higher levels of cancer cell lysis were associated with higher levels of pro-inflammatory cytokines. Both the asymmetric and symmetric bsAbs resulted in higher secretion levels of IFN-γ, TNFα and Granzyme B than anti-VISTA, anti-PD-L1 monotherapy and anti-VISTA/anti-PD-L1 combination therapy.ConclusionThe high level of tumor cell lysis and increased expression of pro-inflammatory cytokines induced by the Fc-based bsAbs suggest a novel approach for the treatment of pancreatic, endometrial and breast cancer.